Cryptosporidium parvum: oocyst excretion and viability patterns in experimentally infected lambs. - Bukhari, Z. (Cambridge University Press, 1997)
Cryptosporidium parvum infections of domestic animals can have a considerable economic impact and as oocysts are voided in the faeces of infected hosts, environmental contamination with agricultural waste has also become a matter of concern. Since only viable oocysts are potentially infectious, the numbers of oocysts excreted during infection can have important implications for both veterinary and public health. During the course of infection in experimentally infected lambs, oocyst viability was assessed by a fluorogenic vital dyes assay and by a maximized in vitro excystation assay. The excreted oocyst populations contained a higher proportion of viable oocysts 5-11 days post infection (d.p.i.) than later in the infection. Oocyst viability declined consistently 11-15 d.p.i. and coincided with periods when peaks in serum and intestinal anti-Cryptosporidium antibodies have been reported to occur. Infected lambs excreted a mean of 4.8 (standard error [S.E.] +/- 0.4) x 10(9) oocysts per g of faeces, of which half were non-viable and therefore of no significance for disease transmission. This study demonstrates that the numbers of viable oocysts excreted by infected lambs is smaller than previously suspected.